First-in-Man Implantation of a New Hybrid Carotid Stent to Prevent Periprocedural Neurological Events During Carotid Artery Stenting. (August 2014) - Schönholz, Claudio; Yamada, Ricardo; Montgomery, William; Brothers, Thomas; Guimaraes, Marcelo
Purpose: To report the initial clinical experience with a new hybrid stent to prevent neurological events during carotid artery stenting. Case Report: A 77-year-old asymptomatic man presented with de novo high-grade stenosis (80%) of the right internal carotid artery (ICA) and occlusion of the contralateral ICA. He was referred for right ICA stenting with a 6/8-mmX40-mm Gore Carotid Stent under cerebral protection using the Gore Carotid Filter. The stent delivery system tracked well over the filter wire and deployment was precise. The result was satisfactory, with 10% residual stenosis. No neurological events occurred during 6 months of follow-up. Conclusion: Initial clinical experience with this new carotid hybrid stent showed satisfactory results, including ease of use, precise deployment, conformability to the wall, and protection against embolization.